(3eMfI GdGeGe CMeO Hf MfHd GdTjHGfis - (3Jbi GdOjf YHO GdZfj Hf YHO GdhGMO Hf SQhQ GdLeGYjdi GdebOSi GdMfHdis
(3ChdgG (B:s
(3GdMeO ddg GdeMehO Ydi cd MGd s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B34s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B357 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B233 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs